Effect of First Long-Term Training on Whole Blood Count and Blood Clotting Parameters in Thoroughbreds - Arianna Miglio; Emanuela Falcinelli; Anna Maria Mezzasoma; Katia Cappelli; Samanta Mecocci; Paolo Gresele; Maria Teresa Antognoni (Animals, 2021)
Training has a strong effect on the physiology of hematological parameters and blood coagulation, both in humans and in horses. Several blood changes have been reported after exercise in horses but available data differ. We aimed to investigate modifications in complete blood count and some hemostatic parameters induced by the first training period in young untrained Thoroughbred racehorses to detect a possible labile blood coagulability in racehorses. Twenty-nine untrained 2-year-old Thoroughbreds were followed during their incremental 4-month sprint exercise schedule. Blood collection was performed once a month, five times (T-30, T0, T30, T60 and T90), before and during the training period for measurement of complete blood count (CBC) and blood clotting parameters (prothrombin time—PT, activated partial prothrombin time—APTT, thrombin clotting time—TCT, fibrinogen—Fb, thrombin–antithrombin complex—TAT). Differences among the time points for each parameter were analyzed (ANOVA, Kruskal–Wallis one-way analysis of variance, p < 0.05). In Thoroughbreds, the first long-term exercise workout period was found to induce a statistical increase in red blood cell indexes and lymphocytes, eosinophils and platelet counts, as well as a hypercoagulability state evident at 30 days of training, which returned to basal levels after 90 days. Regular physical exercise seems to blunt the negative effects of acute efforts on hematological and clotting parameters, an effect that may be attributed to the training condition.